The failure of the government to undermine the rights of the citizens in the general elections - Afdhal, Afdhal (Muhammadiyah Makassar University, 2024)
AbstractThe government in this case a State official with authority in the exercise of government administrative powers is obliged to act neutrally and not permitted for Abuse of authority or abuse of power or in French called the detournement de pouvoir is one of the acts of deviation of the body / office of administration based on the principle of exces de pouvoir (beyond the limits of power) in the concept of rechtsstaat.State officials who want to campaign and conduct campaigns are obliged to apply for leave and not use state facilities so as not to become potential abuse of authority in their duties.A State official who has an interest in campaigning and gives promises to the people is not an agreement so it cannot be categorized as a failure. But when a State official that violates the electoral rules and conduct a campaign using state facilities is considered to be detrimental to the state's finances as described in Constitutional Court Law Recital No. 25/UUXIV/2016Keyword: Government; Campaign; Abuse Of Authority; Benefit Loss;